Nanocellulose-Based Biomaterial Ink Hydrogel for Uptake/Release of Bovine Serum Albumin - Wan Nazihah Liyana, Wan Jusoh; Denesh, Mohan; Mohd Shaiful, Sajab; Peer Mohamed, Abdul; Hatika, Kaco; Gongtao, Ding; Rubiyah, Baini (MDPI, 2023)
This study explores the potential of using nanocellulose extracted from oil palm empty fruit bunch (OPEFB) as a biomaterial ink for 3D printing. The research focuses on using nanocellulose hydrogels for the controlled uptake and release of proteins, with the specific protein solution being Bovine Serum Albumin (BSA). To provide a suitable material for the bioprinting process, the study examines the characteristics and properties of the printed hydrogels through various analyses, such as morphology, functional group, crystallinity, and compression test. Several parameters, such as initial concentration, temperature, and the presence of calcium chloride as an additional crosslinker, affect the protein uptake and release capabilities of the hydrogel. The study is important for biomedicine as it explores the behavior of protein uptake and release using nanocellulose and 3D printing and can serve as a preliminary study for using hydrogels in biological materials or living cells.